Micro-Class teaching of the tourism English course: the smart education in China vocational colleges / Liao Danlu & Fong Pang Chew - Liao, Danlu; Fong, Peng Chew (Universiti Teknologi MARA Cawangan Pahang, 2017)
Smart education becomes the inevitable trend of the global education. With the rapid international tourism development, it becomes a new issue in China to explore how to cultivate qualified tourism graduates with proficient English skills from vocational colleges in terms of smart education. Therefore, this paper aims at discussing China’s current teaching problems of tourism majors’ core course-Tourism English. There are four characteristics of micro-class, namely short-time, fine and concise, interesting, and small-volume resource. The researcher finds raised issues in the teaching classroom include monotonous teaching methods, lack of practice field, inappropriate teaching materials and short of professional teaching staff. In conclusion to solve these problems, the researcher gives three recommendations on Tourism-English micro-class teaching as follows: (1) Realize multiple and open teaching mode, and three dimensions openness of time, space and structure; (2) Increase financial and construction support from the college; (3) Establish the evaluation system of the tourism students' learning achievements in micro-class teaching. As highly information-based the smart education has just started, we should make full use of micro-lesson to improve English Teaching level in vocational colleges, to cultivate students' autonomous learning ability, to cultivate innovative and creative professional tourism talents.